Mutations in γ-secretase subunit–encoding PSENEN gene alone may not be sufficient for the development of acne inversa. Issue 2 (August 2021) - Zhou, Pengjun; Liu, Jingjing; Xu, Tianxing; Guo, Yanni; Han, Yue; He, Yanyan; Lin, Lihang; Xiao, Xuemin
Highlights: Patients with PSENEN mutations revealed decreased expression of PEN2 mRNA and protein. Silencing PSENEN in keratinocytes affected NCT maturation and PS1 phosphorylation. Knockdown of PSENEN in keratinocytes led to the activation EGFR signaling. Silencing PSENEN did not obviously impact proliferation and differentiation of HaCaT. PSENEN mutations alone may be insufficient to cause the development of acne inversa. Abstract: Background: The effects of PSENEN mutations in patients with acne inversa (AI) are poorly understood. Hyperproliferation of follicular keratinocytes and resulting occlusion may constitute the initial pathophysiology. Objective: To investigate the effects of PSENEN knockdown on γ-secretase subunits, biological behaviors, and related signaling pathways in keratinocytes. Methods: HaCaT cells were divided into an experimental group ( PSENEN knock down), a negative control group, and a blank control group. Whole transcriptome sequencing was used to measure differences in mRNA expression of the whole genome; real-time PCR and Western blotting were performed to determine the interference efficiency and the effects of interference on the components of γ-secretase and related molecules. CCK-8 was used to measure cell proliferation, and flow cytometry was used to measure apoptosis and the cell cycle. Results: A comparison of five healthy controls with three patients with PSENEN mutation (c.66delG, c.279delC, c.229_230insCACC) revealed decreased expression of mRNA and protein in skin lesions of the experimental group. In this group, expression of the other components of γ-secretase presenilin C-terminal fragment decreased, expression of immature nicastrin increased, expression of mature nicastrin decreased, and expression of anterior pharynx defective-1 remained unchanged. KEGG analysis revealed that differentially expressed molecules were enriched in m-TOR signaling pathways. Subsequent verification confirmed that differences in PI3K-AKT-mTOR signaling pathway molecules, cell proliferation, apoptosis, cell cycle and the expression levels of Ki-67, KRT1, and IVL between the groups were not statistically significant. Conclusions: PSENEN mutations alone may be insufficient to cause the development of AI, or they may only induce a mild phenotype of AI.